Borgerløn: Kan det nu betale sig? - Kongshøj, Kristian (Politik, 2019)
The idea of basic income has been revitalized in the international debate as a solution to certain problematic trends, including labor market polarization or segmentation. This paper discusses two dominant issues in the debate, namely financing a basic income, and its ability to alleviate labor market segmentation. This means that the normative logics behind basic income with regard to justice, liberty and ecological sustainability will not be discussed. Following insights from the most recent international debate, the paper discusses the dilemma between the adequacy or generosity of basic income on the individual level, and its economic feasibility via taxation. A low or partial basic income model in combination with traditional income benefits could be feasible within the framework of existing tax levels. However, the paper also concludes that segmentation in terms of inequalities in exit and voice opportunities on the labor market is not solved by basic income by itself. Particularly low or partial basic income models may even support such inequalities.